2016
DOI: 10.1016/j.jevs.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Endometrial Injection of Autologous Bone Marrow Mesenchymal Stem Cells in Mares

Abstract: Chronic degenerative endometritis (CDE) is an important cause of fertility problems in older mares. It is estimated that 30% of mares breeding are over 18 years old and the high value of their progeny encourages the use of these animals in assisted reproduction procedures. Currently, cell-based therapies are broadly used in human and veterinary regenerative medicine and have been showed a good effect on the treatment of liver fibrosis. Thus, the present study aimed to evaluate the feasibility and safety of end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
1
8
0
3
Order By: Relevance
“…In both experiments, no clinical abnormalities were found in the application sites of allogeneic MSCs, which demonstrate the safety of this procedure, as reported by Alvarenga et al (), Maia et al (), Ferris et al (), Carradeet al() and Kol et al () using this therapy in other tissues.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In both experiments, no clinical abnormalities were found in the application sites of allogeneic MSCs, which demonstrate the safety of this procedure, as reported by Alvarenga et al (), Maia et al (), Ferris et al (), Carradeet al() and Kol et al () using this therapy in other tissues.…”
Section: Discussionsupporting
confidence: 83%
“…In horses, MSCs therapy focused mainly on osteoarticular, tendinous lesions (Guest, Ousey, & Smith, ; Taylor, Smith, & Clegg, ) and intra‐articular injection (Ferris et al, ), with few reports of their use in other tissues. However, some studies demonstrated therapeutic benefits when MSCs were used in the uterus (Alvarenga et al, ). On the other hand, in equine testicles, there is a complete lack of information concerning MSCs administration.…”
Section: Introductionmentioning
confidence: 99%
“…Injection [340] or infusion [341] of MSCs has been described as a possible alternative for the treatment of endometrial fibrosis. Therapy with MSCs can induce an early (7 days) and also a prolonged (60 days) remodeling of the endometrium of mares suffering from chronic-degenerative endometriosis by modulating the expression patterns (e.g., cytokeratin, vimentin, α-smooth muscle actin, and laminin) associated with the development of pathological fibrosis in the horse endometrium, as well as promoting glandular epithelial cells proliferation [341].…”
Section: Stem Cellsmentioning
confidence: 99%
“…Apesar de a endometriose ser uma patologia degenerativa irreversível, existem estudos que avaliam a eficácia de alguns tratamentos para essa afecção uterina (Alvarenga et al, 2016, Mambelli et al, 2014. Um dos tratamentos para endometriose em éguas mais recentemente que tem sido estudado é com o uso de células tronco mesenquimais.…”
Section: Tratamentosunclassified